Credence - Douglas, Penelope, 1977- (Berkley Romance, 2024)
"Tiernan de Haas doesn't care about anything anymore. The only child of a film producer and his starlet wife, she's grown up with wealth and privilege but not love or guidance. Shipped off to boarding schools from an early age, it was impossible to escape the loneliness and carve out a life of her own. And when they suddenly pass away, she knows she should be devastated. But has anything really changed? She's always been alone, hasn't she? Jake Van der Berg, her father's stepbrother and her only living relative, assumes guardianship of Tiernan. Sent to live with Jake and his two sons, Noah and Kaleb, in the mountains of Colorado, Tiernan quickly learns that these men now have a say in what she chooses to care and not care about anymore. As the three men take Tiernan under their wing, she slowly finds her place among them...and as a part of them. Because lines blur and rules become easy to break when no one else is watching. One of them has her. The other one wants her. But he's going to keep her."--